Compact form and evaluation of Trubnikov’s plasma dielectric tensor - Pavlov, S.S.; Castejon, F. (Вопросы атомной науки и техники, 2005)
Trubnikov’s plasma dielectric tensor by means of integral transform is reduced to more simple and transperant form. Due that the problem evaluating this tensor for arbitrary plasma temperature and the angle of wave propagation is resolved. Розв'язується проблема точного обчислення плазмового діелектричного тензору Трубнікова для довільних значень температури плазми і кута розповсюдження в ній хвиль. Решается проблема точного вычисления Трубниковского плазменного диэлектрического тензора для произвольных значений температуры плазмы и угла распространения в ней волн.